2021
DOI: 10.1037/gdn0000150
|View full text |Cite
|
Sign up to set email alerts
|

Ruptures and repairs in group psychotherapy: Introduction to the special issue.

Abstract: Objectives: All relationships experience tensions and ruptures, but not all ruptures are acknowledged and repaired. Individual therapy researchers have shown that repairing ruptures in the therapy relationship is associated with an increased alliance, decreased dropout, and positive treatment outcome. Until recently, there has been less attention paid to ruptures in group psychotherapy. The current special issue is devoted to theory, assessment, research, and practice regarding ruptures and repairs in group tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Regarding future research directions, our findings may support the relevance of examining the complex aspects of alliance rupture repair processes in group therapy (Lo Coco et al, 2019; Marmarosh, 2021). Only one evidence-based case study has examined the feasibility of using the Rupture Resolution Rating System (3RS; Eubanks et al, 2015) in group therapy (Garceau et al, 2021) and found that most ruptures occurred between members, and that one-third of all repairs were initiated by members.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Regarding future research directions, our findings may support the relevance of examining the complex aspects of alliance rupture repair processes in group therapy (Lo Coco et al, 2019; Marmarosh, 2021). Only one evidence-based case study has examined the feasibility of using the Rupture Resolution Rating System (3RS; Eubanks et al, 2015) in group therapy (Garceau et al, 2021) and found that most ruptures occurred between members, and that one-third of all repairs were initiated by members.…”
Section: Discussionsupporting
confidence: 53%
“…However, the meta-analytic evidence regarding the association between group process factors and outcome is still limited. Group psychotherapy researchers have examined the relationship between cohesion and outcome extensively (Burlingame et al, 2018), but they have paid less attention to the alliance in group therapy (Marmarosh, 2021). Recently, a first meta-analysis of 29 studies of member-to-therapist alliance in group therapies (Alldredge et al, 2021) showed that the alliance was significantly associated with outcomes with a small effect ( r = .17).…”
Section: The Alliance Concept In Group Therapymentioning
confidence: 99%
“…Is the membership stable over time? Does the group deal with conflict effectively (e.g., Marmarosh, 2021)? Cohesion can also be intuited from direct observation of the group's communication and interaction patterns, as language use, influence tactics, conflict levels, and modes of resolving conflict likely differ systematically in relationship to a group's cohesion.…”
Section: Assessing Cohesionmentioning
confidence: 99%
“…In essence, group members can be quiet and observing the interaction between other group members and the leaders. These bystanders members who are not directly involved in a rupture nevertheless can experience the effects of ruptures occurring to other members (Marmarosh, 2021c). For example, a group member experiences anger when a fellow group member interrupts them.…”
Section: Bystander Rupturesmentioning
confidence: 99%